Penguatan Karakter Siswa Melalui Profil Pelajar Pancasila Dimensi Beriman dan Bertaqwa kepada Tuhan Yang Maha Esa dan Berakhlak Mulia - Thusyadia , Vidya Halima; Hutami, Etika Moral; Patmisari, Patmisari (Buletin Literasi Budaya Sekolah, 2024)
Indonesia has diversity starting from customs, languages, religions and ethnic groups, which must be preserved, and one of them is being able to maintain the character of having faith and devotion to God Almighty and having good morals to live in the surrounding environment for oneself and many people. Religion is inherent in Indonesian citizens from all walks of life, and students have begun to receive religious education from an early age. Promoting religious education is an important part of the growth and development process of children and students. In essence, strengthening the character of students is an urgency for educators. Strengthening character is an activity that is useful for developing abilities in forming character, which aims to educate and develop good character. In this strengthening process, many ways can be done, one of which is by strengthening character through positive religious activities and building a character that is devout and obedient. As educators and places to get a better education, schools facilitate the strengthening of obedient character.